Case study of a model of local solar radiation potential and discussion on the associated sustainable applications and potentials (Sustainability in Debate, 2020)
The demand for a sustainable transition to energy matrices of lower environmental impact is global and current. In this sense, the modelling of solar radiation in high spatial resolution is used to assess the potential of photovoltaic generation on any type of surface and provide information for the planning and dimensioning of photovoltaic systems. From the technical potential of generation, it is possible to estimate the systems payback time and the avoided greenhouse gas emissions when adopting photovoltaic energy. In the quantitative context, the objective of this article was to briefly address the technical methodology and build a model of solar radiation of EE-IGC-UFMG buildings. In the context of sustainable applications of the tool, the objective was to address relevant topics, such as the construction of radiation models and the associated potentials, the application scales, and the difficulties and limitations of the modelling.